Corn stover semi-mechanistic enzymatic hydrolysis model with tight parameter confidence intervals for model-based process design and optimization. (February 2015) - Scott, Felipe; Li, Muyang; Williams, Daniel L.; Conejeros, Raúl; Hodge, David B.; Aroca, Germán
Highlights: A semi-mechanistic model is proposed for pretreated corn stover saccharification. The model considers high-solid saccharification and washed or unwashed solids. A subset of identifiable parameters was found showing tight confidence intervals. Uncertainty in parameters estimates was used to predict bands for glucose yield. The model reliably describes the saccharification kinetics of corn stover' glucan. Abstract: Uncertainty associated to the estimated values of the parameters in a model is a key piece of information for decision makers and model users. However, this information is typically not reported or the confidence intervals are too large to be useful. A semi-mechanistic model for the enzymatic saccharification of dilute acid pretreated corn stover is proposed in this work, the model is a modification of an existing one providing a statistically significant improved fit towards a set of experimental data that includes varying initial solid loadings (10–25% w/w) and the use of the pretreatment liquor and washed solids with or without supplementation of key inhibitors. A subset of 8 out of 17 parameters was identified, showing sufficiently tight confidence intervals to be used in uncertainty propagation and model analysis, without requiring interval truncation via expert judgment.